2010
DOI: 10.1038/nm.2142
|View full text |Cite
|
Sign up to set email alerts
|

Memory CD4+ T cells induce innate responses independently of pathogen

Abstract: Inflammation induced by recognition of pathogen-associated molecular patterns dramatically impacts subsequent adaptive responses. We asked if the adaptive immune system can also affect the character and magnitude of innate inflammatory responses. We find that the response of memory, but not naïve, CD4+ T cells enhances production of multiple innate inflammatory cytokines and chemokines (IIC) in the lung, and that during influenza infection, this leads to early control of virus. Memory CD4+ T cell induced IIC a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
176
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 165 publications
(198 citation statements)
references
References 50 publications
17
176
0
5
Order By: Relevance
“…In agreement with studies using in vitro-generated memory cells (19), in vivo PR8 memory cells upregulated CD69 1-2 d earlier in the lung and draining lymph nodes (dLN) than did naive cells (Fig. 1A), indicating a more rapid activation of memory cells, but 4 d postinfection (dpi) the expansion of naive and memory donors was similar (Fig.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…In agreement with studies using in vitro-generated memory cells (19), in vivo PR8 memory cells upregulated CD69 1-2 d earlier in the lung and draining lymph nodes (dLN) than did naive cells (Fig. 1A), indicating a more rapid activation of memory cells, but 4 d postinfection (dpi) the expansion of naive and memory donors was similar (Fig.…”
Section: Resultssupporting
confidence: 88%
“…2D). This result stresses the necessity of late-acting events and also is consistent with some protective contribution from earlier-acting memory cell functions (19). These results suggest that 2°effectors are key contributors to memory CD4 + T-cell-mediated protection against IAV.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…For instance, Swain and colleagues observed that transferring memory IAV-specific CD4 cells into naive mice could prime an IAV response without the need for TLR activation. 21 Data from research into heterologous immunity of adult mice and humans, as well as epidemiological data from vaccination studies of children, suggest that the sequence of infection or vaccination can lead to either detrimental or beneficial effects on subsequent unrelated infections. These data would be consistent with the idea that they play a role in the education of the immune system and that there may be a more optimum vaccination strategy, which would be beneficial to the maturation of the immune system.…”
Section: Neonatal Tcr Repertoirementioning
confidence: 99%